2010
DOI: 10.1177/0020872809358399
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary collaboration in social work education in the USA, Israel and Canada: Deans’ and directors’ perspectives

Abstract: This article utilized survey research to examine where interdisciplinary collaboration is occurring and being taught in social work programs in three countries. Findings indicate that social work programs participate in high levels of interdisciplinary collaboration at the university—community level and the interdepartmental level and teach it through an array of courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Consistent with Berg-Weger and Schneider's research, this survey shows that psychology and education continue to rank high among the disciplines partnering with social work for interdisciplinary collaborations. Bronstein et al (2010) found interdisciplinary trends in social work growing most rapidly in the fields of law, nursing, medicine, and public health. The literature on academic interdisciplinary social work supports this finding.…”
mentioning
confidence: 99%
“…Consistent with Berg-Weger and Schneider's research, this survey shows that psychology and education continue to rank high among the disciplines partnering with social work for interdisciplinary collaborations. Bronstein et al (2010) found interdisciplinary trends in social work growing most rapidly in the fields of law, nursing, medicine, and public health. The literature on academic interdisciplinary social work supports this finding.…”
mentioning
confidence: 99%
“…IPE does not simply entail students from multiple disciplines receiving the same learning experience, nor is it faculty from one field teaching or mentoring students from another; rather, it is a fully integrated or shared learning and decision-making process (Buring et al, 2009). Whereas interest in promoting IPE within BSW and MSW programs appears to be increasing, evidence suggests that few social work programs incorporate interprofessional learning as an integrated component of the curriculum (Bronstein et al, 2010;McPherson, Headrick, & Moss, 2001;Reeves et al, 2010).…”
Section: Interprofessional Education and Social Workmentioning
confidence: 99%
“…Though most of these articles are exclusively conceptual or descriptive, they represent efforts at organized collaboration between social work and a wide variety of disciplines including nursing, medicine, dentistry, occupational therapy, physical therapy, pharmacy, chaplaincy, education, nutrition, and law. In social work, dual degree programs and/or formal teaching arrangements are particularly common approaches to IPE (Bronstein et al, 2010;Simms, 2011). Other popular strategies found in the social work literature include one-time seminars and year-long field education experiences, although examples of more longitudinal, integrated programs also exist (Pecukonis et al, 2013).…”
Section: Interprofessional Education and Social Workmentioning
confidence: 99%
“…Following Bronstein (2003) and Bronstein et al (2010), the definition of interdisciplinarity used in this research goes further insofar as it requires such an effective interpersonal process facilitating the achievement of goals, which could not be reached if individual professionals acted on their own.…”
Section: Interdisciplinarity and Social Work Trainingmentioning
confidence: 99%
“…These were taken into account and incorporated in the surveys conducted recently in Canada, Israel and the US (Bronstein et al, 2010), then in Hungary, and in 2011 are being undertaken in Japan.…”
Section: Research Methologymentioning
confidence: 99%